Acquisition et évaluation des compétences des enfants instruits hors institution scolaire - Bernadette Nozarian (Éducation et Socialisation)
In France, families manage Unschooling despite the legal and practical complication they face. Is it legitimate for the National Education Office to monitor children, who do not study at school? This survey is about how unschoolers learn, which skills they learn, and what we could do to improve the French situation which has become critical.